SIMPLE ADDITIVE WEIGHTING METHOD DECISION SUPPORT SYSTEM IN CEMENT SELECTION AT UD.WENDY JAYA - Nazryani, Della; Fauziah, Rizky; Yuma, Febby Madonna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: Technology is a tool for processing, storing and modifying data to obtain informatio. Decision Support System (DSS) a based model-based with data processing procedures and considerations to assist manager in decision making. In the context of UD.Wendy Jaya which still uses manual methods for selecting superior cement, this is considered less effective and ineffcient, resulting in cement selection that does not meet the criteria and lacks accuracy. This research employs a quantitative method with the aim of determining decisions for selecting superior cemen and designing a decision support system using the Simple Additive Weighting (SAW) method based on predetermined criteria. The implementation result show that the decision support system for determining superior cement provides convenience and speed in selecting superior cement at UD Wendy Jaya according to the expected criteria. The results of calculations using the simple additive weighting (SAW) method rank each alternative, with the most superior alternative being three-wheel cement, considering several criteria such as price, compressive, strength, fineness, water capacity and setting time.Keywords: simple additive weighting (SAW); decision support system; UD.wendy jayaAbstrak: Teknologi adalah alat untuk mengolah, menyimpan, dan memodifikasi data guna mendapatkan informasi. Sistem Pendukung Keputusan (Decision Support System/DSS) merupakan sistem berbasis model dengan prosedur pemrosesan data dan pertimbangan untuk membantu manajer dalam pengambilan keputusan. Dalam konteks Toko UD. Wendy Jaya, yang masih menggunakan cara manual untuk pemilihan semen unggul, hal ini dianggap kurang efektif dan tidak efisien, mengakibatkan pemilihan semen tidak sesuai kriteria dan tidak akurat. Penelitian ini menggunakan metode kuantitatif, dengan tujuan untuk mengetahui keputusan pemilihan semen unggul dan merancang sistem pendukung keputusan menggunakan metode Simple Additive Weighting (SAW) berdasarkan kriteria yang ditentukan. Hasil implementasi menunjukkan bahwa sistem pendukung keputusan Menentukan Semen Unggul memberikan kemudahan dan kecepatan dalam pemilihan semen unggul pada Toko UD. Wendy Jaya sesuai dengan kriteria yang diharapkan. Hasil dari perhitungan dengan menggunakan metode Simple Additive Weighting (SAW) adalah perangkingan setiap alternatif yaitu diperoleh alternatif yang paling unggul adalah semen tiga roda ditinjau dari beberapa kriteria harga, kuat tekanan, kehalusan, kapasitas air dan waktu mengeras.Kata kunci: simple additive weighting (SAW); sistem pendukung keputusan; UD.wendy jaya